A Study on the Diagnosis of Lumbar Spinal Malposition in Chuna Manual Therapy Using X-Ray Images Based on Digital Markers - Min-Su Ju; Tae-Yong Park; Minho Choi; Younseok Ko; Young Cheol Na; Yeong Ha Jeong; Jun-Su Jang; Jin-Hyun Lee (Diagnostics, 2025)
Background/Objectives: This study aimed to evaluate digital markers and establish quantitative diagnostic criteria for spinal malpositions in Chuna manual therapy using lumbar X-rays. Methods: A total of 2000 X-ray images were collected from adult patients at the International St. Mary’s Hospital of Catholic Kwandong University. Five Chuna manual medicine experts annotated anatomical landmarks using a digital marker labeling program and diagnosed three types of spinal malpositions: flexion/extension, lateral bending, and rotation. Diagnostic accuracy was evaluated using weighted F1 (F1_W) scores, and the optimal threshold values for each malposition type were determined based on maximum F1_W performance. Results: The results showed high diagnostic performance, with average maximum F1_W scores of 0.76 for flexion/extension, 0.85 for lateral bending, and 0.71 for rotation. Based on this analysis, threshold angles for each type of spinal malposition in Chuna manual diagnosis were determined. Conclusions: This study demonstrates the diagnostic validity of digital marker-based X-ray analysis in Chuna manual therapy and is the first to propose quantitative diagnostic thresholds for spinal malpositions. These findings may serve as a foundation for clinical application in spinal assessment and treatment planning, with further validation studies warranted.